2009
DOI: 10.1007/s00439-009-0687-9
|View full text |Cite
|
Sign up to set email alerts
|

Gross deletions/duplications in PROS1 are relatively common in point mutation-negative hereditary protein S deficiency

Abstract: Hereditary protein S (PS) deficiency is an autosomal disorder caused by mutations in the PS gene (PROS1). Conventional PCR-based mutation detection identifies PROS1 point mutations in approximately 50% of the cases. To verify if gross copy number variations (CNVs) are often present in point mutation-negative hereditary PS deficiency we used multiplex ligation-dependent probe amplification (MLPA) as a detection tool in samples from individuals with a high probability of having true PS deficiency. To this end, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 37 publications
4
33
1
3
Order By: Relevance
“…Using quantitative PCR, Johansson et al [46] found large deletions in 3 out of 8 ProS-deficient families (37.5%) who were PROS1 gene mutation-negative. Pintao et al [35] identified gross abnormalities in 6 out of 18 probands (33.3%) who were mutation-negative and suggested that MLPA is a useful tool to uncover gross mutations. Furthermore, LindHalld en et al [47] detected large deletions in 5 out of 8 families (62.5%) that were previously sequenced and identified no mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using quantitative PCR, Johansson et al [46] found large deletions in 3 out of 8 ProS-deficient families (37.5%) who were PROS1 gene mutation-negative. Pintao et al [35] identified gross abnormalities in 6 out of 18 probands (33.3%) who were mutation-negative and suggested that MLPA is a useful tool to uncover gross mutations. Furthermore, LindHalld en et al [47] detected large deletions in 5 out of 8 families (62.5%) that were previously sequenced and identified no mutations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, multiplex ligationdependent probe amplification (MLPA) was employed to detect large or gross variations of the PROS1 gene in cases in which no mutation was detected by direct sequencing, but repeatedly low ProS activity suggested a genetically determined deficiency. For this analysis, the SALSA MLPA P112 PROS1 kit (MRC-Holland, Amsterdam, Netherlands) was used [35]. It contains 15 probes for 12 of the 15 exons, one probe for the promoter region and one probe for the potential exon 4 of the ProS pseudogene.…”
Section: The Pros1 Gene Analysismentioning
confidence: 99%
“…Type I PS deficiency is most frequently observed and often a consequence of missense mutations in the protein S gene (PROS1). Copy number variations were found in 33% of a group of missense negative patients with PS deficiency (Pintao et al, 2009). These copy number variations included deletion of the whole PROS1 gene, partial gene deletions and partial duplications.…”
Section: Antithrombin Deficiencymentioning
confidence: 99%
“…In the PROSIT study, mutations in PROS1 were found only in 70% of probands with PS deficiency (17). However, using DNA sequencing methods, large deletions or gene segment duplications may remain undetected (74,75). Moreover, there are mutations affecting the transcription regulatory sequences at the 5' of the gene (76,77).…”
Section: Protein S Deficiencymentioning
confidence: 99%